Revised burst model for pipeline integrity assessment. (October 2017) - Liu, Hanwen; Khan, Faisal; Thodi, Premkumar
Abstract: Failure of pipeline is often caused by corrosion. It affects the health, safety, environment and economy considerably. To prevent pipeline failure, it is necessary to focus on the corrosion and pressure of the structures. Burst pressure is a key factor to assess the integrity of a pipeline. There are three means to determine burst pressure. These are lab testing, evaluation criteria and the Finite Element Method (FEM) modeling. However, the results of the burst pressure assessment using evaluation criteria are too conservative compared to the results of an actual pipe burst experiment and FEM modeling. The objectives of this paper are to analyze the changing trend of burst pressure of pipelines with different defect dimensions; to compare the FEM results with those of the evaluated criteria (DNV model) to indicate the conservative property; to revise the DNV model and verify its validity with actual burst experiments. The revised DNV model predicts burst pressure more reliably that could result in better engineering design of pipelines. Highlights: A novel consideration of multiple defects in design evaluation Revisions in the DNV model to account number of defects Testing and validation of the proposed revision in the DNV model